Apple Cultivation - Recent Advances 2023
DOI: 10.5772/intechopen.109429
|View full text |Cite
|
Sign up to set email alerts
|

Apple Production under Protective Netting Systems

Abstract: Apple crop is more and more cultivated under protective netting systems. Depending on the location and sunlight intensity, apple orchards can benefit from these installations, as they will be protected against extreme weather events. Depending on the technical features of the thread, the nets will be hail-proof, wind-proof, or rain-proof, while having different shading percentages. Modern fruit production faces high pressure also related to biotic stressors; thus, modern protective nets are designed to aid pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
(97 reference statements)
0
3
0
Order By: Relevance
“…The microclimatic impact of colored shading nets on the reduction in photosynthetically active radiation (PAR) has the potential to significantly impact the key physiological processes determining fruit yield and quality in crops, including photosynthesis and carbon allocation [35]. The variations in PAR availability observed among the different nets stem from the color of threads, which alters the proportion of diffuse light compared to the total light transmitted under nets [36].…”
Section: Photosynthetically Active Radiation (Par)mentioning
confidence: 99%
See 1 more Smart Citation
“…The microclimatic impact of colored shading nets on the reduction in photosynthetically active radiation (PAR) has the potential to significantly impact the key physiological processes determining fruit yield and quality in crops, including photosynthesis and carbon allocation [35]. The variations in PAR availability observed among the different nets stem from the color of threads, which alters the proportion of diffuse light compared to the total light transmitted under nets [36].…”
Section: Photosynthetically Active Radiation (Par)mentioning
confidence: 99%
“…x FOR PEER REVIEW 9 of 20 availability observed among the different nets stem from the color of threads, which alters the proportion of diffuse light compared to the total light transmitted under nets[36].…”
mentioning
confidence: 99%
“…The most commonly used protection systems are roof covers and high tunnels, which protect crops from rain and frost, in turn accelerating fruit maturity and advancing the harvest date [4]. Furthermore, netting is also an effective tool to protect orchards from sunburn, hailstorms, and insect attacks [5].…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly used materials in rain-protection systems are waterproof woven covers with a laminated texture or low-density polyethylene (LDPE) plastic covers with a smooth texture, while porous and permeable raschel or monofilament nets are used for netting [5,6]. Ogden and van Iersel [7] evaluated LDPE plastic covers for 'Emerald' and 'Jewel' blueberry cultivars and concluded that this type of cover affected the synchronization of flowering and pollination, thus decreasing fruit set and yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation